VD_FINDINFO Jug / 2012 / 33 vom 30. August 2011 - VD Tribunal cantonal (2011)
COMPLICITÉ, LOI FÉDÉRALE SUR LES STUPÉFIANTS ET LES SUBSTANCES PSYCHOTROPES | 25 CP, 19 ch. 1 al. 4 LStup, 19 ch. 1 al. 5 LStup, 19 ch. 1 al. 6 LStup